De-hospitalization of the pediatric day surgery by means of a freestanding surgery center: pilot study in the lazio region - Mangia Giovanni; Bianco Franco; Ciaschi Alma; Caro Elisabetta; Frattarelli Eufrasia; Marrocco Giacinto (BMC, 2012)
Abstract Background Day surgery should take place in appropriate organizational settings. In the presence of high volumes, the organizational models of the Lazio Region are represented by either Day Surgery Units within continuous-cycle hospitals or day-cycle Day Surgery Centers. This pilot study presents the regional volumes provided in 2010 and the additional volumes that could be provided based on the best performance criterion with a view to suggesting the setting up of a regional Freestanding Center of Pediatric Day Surgery. Methods This is an observational retrospective study. The activity volumes have been assessed by means of a DRG (Diagnosis Related Group)-specific indicator that measures the ratio of outpatients to the total number of treated patients (freestanding indicator, FI). The included DRGs had an FI exceeding the 3rd quartile present in at least a health-care facility and a volume exceeding 0.5% of the total patients of the pediatric surgery and urology facilities of the Lazio Region. The relevant data have been provided by the Public Health Agency and relate to 2010. The best performance FI has been used to calculate the theoretical volume of transferability of the remaining facilities into freestanding surgery centers. Patients under six months of age and DRGs common to other disciplines have been excluded. The Chi Square test has been used to compare the FI of the health-care facilities and the FI of the places of origin of the patients. Results The DRG provided in 2010 amounted to a total of 5768 belonging to 121 types of procedures. The application of the criteria of inclusion have led to the selection of seven final DRG categories of minor surgery amounting to 3522 cases. Out of this total number, there were 2828 outpatients and 694 inpatients. The recourse of the best performance determines a potential transfer of 497 cases. The total outpatient volume is 57%. The Chi Square test has pointed to a statistically significant difference of the facilities and to a non-significant difference of inferiority of the regional places of origin with respect to the city of Rome. Conclusions The activity volumes would seem to support the setting up of a Freestanding Regional Center of Pediatric Day Surgery. This Center represents the healthcare facility that is most likely to allow a de-hospitalization process. Subsequent studies will be required to confirm the validity of this pilot study.